2020
DOI: 10.1109/jtehm.2020.2985026
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Clinical Parameters Sensitive to Functional Voice Disorders Applying Boosted Decision Stumps

Abstract: Background: Various voice assessment tools, such as questionnaires and aerodynamic voice characteristics, can be used to assess vocal function of individuals. However, not much is known about the best combinations of these parameters in identification of functional dysphonia in clinical settings. Methods: This study investigated six scores from clinically commonly used questionnaires and seven acoustic parameters. 514 females and 277 males were analyzed. The subjects were divided into three groups: one healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…This may then lead to changes in the shape of the parameter distribution in comparison to healthy subjects. In summary, single parameters are not suitable for differentiating healthy from FD subjects and multi-parametric approaches are needed as suggested before [ 38 , 59 , 60 ]. However, if not FD in general but subcategories of FD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This may then lead to changes in the shape of the parameter distribution in comparison to healthy subjects. In summary, single parameters are not suitable for differentiating healthy from FD subjects and multi-parametric approaches are needed as suggested before [ 38 , 59 , 60 ]. However, if not FD in general but subcategories of FD (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Patrick Schlegel et al conducted a study to identify clinical parameters that are sensitive to functional voice disorders using boosted decision stumps. Their findings indicated that a smaller subset of parameters (specifically, 4 out of 13) was effective in distinguishing between three groups: one healthy group and two groups with voice disorders [17]. However, these studies have been limited in terms of considering the association between prognostic factors and the outcomes of speech therapy.…”
Section: Introductionmentioning
confidence: 99%